Accessibility of TV media for the dual-sensory impaired in Finland and in the UK - Stina Ojala; Russ Palmer; Riitta Lahtinen (Sosiaali- ja terveyshuollon tietojenkäsittely-yhdistys, 2022)
One of the most used media is television. Almost all of us have a television set at home. Television is commonly thought also to be accessible, and for most of us, it seems to be so. However, there are people who cannot enjoy televised programmes without special measures. These measures include subtitling, audio description and sign language interpretation. All these are mentioned in the in-force EU Audiovisual Media Services Directive.
In this article we look at how these are broadcast in different countries, what equipment is needed for receiving them, and how accessible the programme information (EPG) and menus to choose these accessibility options are, as they most often are not automatic, but have to be turned on in the accessibility options menu or the TV set or digital terrestrial receiver box (digibox). This article focuses on accessibility with special interest on the dual-sensory impaired perspective over four days comparing two countries: the UK where all three accessibility features mentioned above are well-established and Finland, where accessibility features concentrate mainly on subtitling.